Analisis Ekspor Indonesia Ke Jepang - Dewi Mahrani Rangkuty (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2018)
Japan is one of developed countries had been Indonesian fixed consumer at international market. High value exports an country would be increasing domestic economic growth because international trade (exports-imports) as component for economic growth. Indonesia’s export for Japan has fluctuation growth rate for this research period. This research has aimed for analyze Indonesia’s export to Japan and GDP Japan with time series 1987-2017. The result of counteraction test showed no equilibrium relation for long term between Indonesia’s export and GDP Japan. And with granger causality test showed for Lag 2 and 5 Indonesia’s export to Japan and GDP Japan showed two-way direction. It means Indonesia’s export to Japan has influence GDP Japan and GDP Japan has influence Indonesia’ export to Japan in this research period. In recommended for government as the Indonesian trade ministry hopely could keep growth rate stability of Indonesia’s export to Japan because Japan has one of developed country as Indonesian fixed partner at international market, and the goals for equilibrium relation for long term between Indonesia’s export to Japan and GDP Japan.